ANALYSIS AND COMPARISON OF GRAVITY ANOMALIES FROM THE GLOBAL GEOPOTENTIAL MODELS EGM 2008 AND EIGEN- 6C4 WITH AVAILABLE GRAVITY ANOMALIES IN AN EXTREMELY MOUNTAINOUS REGION OF THE TERRITORY OF SOUTHWEST BULGARIA - RILA MOUNTAIN: ANALYSIS AND COMPARISON OF GRAVITY ANOMALIES FROM THE GLOBAL GEOPOTENTIAL MODELS EGM 2008 AND EIGEN- 6C4 WITH AVAILABLE GRAVITY ANOMALIES IN AN EXTREMELY MOUNTAINOUS REGION OF THE TERRITORY OF SOUTHWEST BULGARIA - RILA MOUNTAIN - Kirilova, Krasimira (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The subject of the study is the analysis of the Bouguer gravity anomaly and its comparison by comparing the Bouguer anomaly values from the global geopotential models (GGMs) EGM 2008 and EIGEN-6C4 with data from interpolated values of 46,121 points for the Rila Mountain region, in which GNSS/leveling measurements have been carried out. The Bouguer anomaly map gives a good idea of the subsurface density [7]. In mountainous areas, topographic effects completely dominate local variations in the gravity field, so it is necessary to introduce local topographic reductions to remove this dependence on height.